Grape Seed Extract Polyphenols Improve Resistance Artery Function in Pregnant eNOS–/– Mice - Tropea, Teresa; Greenwood, Susan L.; Sibley, Colin P.; Cottrell, Elizabeth C. (Frontiers in Physiology, 2020)
Hypertension during pregnancy is a leading cause of maternal and fetal morbidity and mortality worldwide, increasing the risk of complications including preeclampsia, intracerebral haemorrhage and fetal growth restriction. Increased oxidative stress is known to contribute to poor vascular function; however, trials of antioxidant supplementation have raised concerns about fetal outcomes, including risk of low birthweight. Grape seed extract polyphenols (GSEP) have been suggested to promote cardiovascular protection, at least in part through antioxidant actions. We tested the hypothesis that administration of GSEP during pregnancy would reduce oxidative stress and improve resistance artery function with no detrimental effects on fetal growth, in an established model of maternal hypertension associated with vascular dysfunction, the endothelial NO synthase knockout (eNOS-/-) mouse. Pregnant C57BL/6J (WT) and eNOS-/- mice received either GSEP (200 mg/kg/day) or drinking water, between gestational (GD) day 10.5 and GD18.5. At GD17.5, maternal systolic blood pressure (SBP) was measured; at GD18.5, maternal malondialdehyde (MDA) concentrations, vascular function of aortic, mesenteric, uterine and posterior cerebral arteries was assessed, and fetal outcome evaluated. GSEP reduced maternal SBP and plasma MDA concentrations in eNOS-/- mice. Whilst there was no effect of GSEP on vascular reactivity of aortas, GSEP improved endothelial-dependent relaxation in mesenteric and uterine arteries of eNOS-/- mice and normalised lumen diameters of pressurised posterior cerebral arteries in eNOS-/- mice. Supplementation with GSEP had no effect in WT mice and did not affect fetal outcomes in either genotype. Our data suggest that GSEP improve resistance artery function, potentially through antioxidant actions, and provide a basis to further investigate these beneficial effects including in the prevention of intracerebral haemorrhage. Maternal supplementation with GSEP may be a safe intervention to improve outcomes in pregnancies associated with hypertension and vascular dysfunction.